Mechanism of Pb(ii) and methylene blue adsorption onto magnetic carbonate hydroxyapatite/graphene oxide. Issue 13 (14th February 2015) - Cui, Limei; Wang, Yaoguang; Hu, Lihua; Gao, Liang; Du, Bin; Wei, Qin
<x xml:space="preserve">Abstract</x> Magnetic carbonate hydroxyapatite was loaded onto GO sheets to obtain a novel adsorbent for the removal of heavy metals and dyes.